2021
DOI: 10.1016/j.sjbs.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

In silico annotation of unreviewed acetylcholinesterase (AChE) in some lepidopteran insect pest species reveals the causes of insecticide resistance

Abstract: Lepidoptera is the second most diverse insect order outnumbered only by the Coeleptera. Acetylcholinesterase (AChE) is the major target site for insecticides. Extensive use of insecticides, to inhibit the function of this enzyme, have resulted in the development of insecticide resistance. Complete knowledge of the target proteins is very important to know the cause of resistance. Computational annotation of insect acetylcholinesterase can be helpful for the characterization of this important protein. Acetylcho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…The compounds isolated from the two Diospyros species (3, 4, 5, 11, 12, 13, 14, 17, 18, 20), origanal (21), limonin (22), were tested for AChE inhibitory activity, using the insecticide phorate sulfoxide (23) as positive reference, since organophosphate insecticides act as AChE inhibitors by their binding to the catalytic site in this protein. [51] Published reports have indicated that AChE is a key target in the resistance mechanisms developed by Lepidoptera such as S. frugiperda, [52] therefore, we chose to use this protein as a model in this work. Most of the compounds displayed relatively low percentages of inhibition (Table 3), therefore, the media inhibitory concentration (IC 50 ) values were calculated only for those compounds with 50 % or greater inhibition ( 21) is related to the decrease of the activity as an inhibitor of AChE.…”
Section: Acetylcholinesterase Inhibitory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds isolated from the two Diospyros species (3, 4, 5, 11, 12, 13, 14, 17, 18, 20), origanal (21), limonin (22), were tested for AChE inhibitory activity, using the insecticide phorate sulfoxide (23) as positive reference, since organophosphate insecticides act as AChE inhibitors by their binding to the catalytic site in this protein. [51] Published reports have indicated that AChE is a key target in the resistance mechanisms developed by Lepidoptera such as S. frugiperda, [52] therefore, we chose to use this protein as a model in this work. Most of the compounds displayed relatively low percentages of inhibition (Table 3), therefore, the media inhibitory concentration (IC 50 ) values were calculated only for those compounds with 50 % or greater inhibition ( 21) is related to the decrease of the activity as an inhibitor of AChE.…”
Section: Acetylcholinesterase Inhibitory Activitymentioning
confidence: 99%
“…Interestingly, the AChE inhibitory activity for betulinic acid (11) has been reported in the context of research on therapeutic substances against Alzheimer's disease using the model of AChE from Torpedo californica. [52]…”
Section: Acetylcholinesterase Inhibitory Activitymentioning
confidence: 99%
“…For example, the insect heart rate and contraction are regulated by glutamate and other neurotransmitters including ACh, norepinephrine, dopamine, serotonin and octopamine [ 66 ]. ACh is a key excitatory neurotransmitter in the insect nervous system [ 67 ].…”
Section: Malaria Vector Controlmentioning
confidence: 99%
“…The catalytic serine (Ser 360 ; Figure 3 A) is the target for covalent insecticides, including organophosphates and carbamates [ 61 , 62 ]. These insecticides establish a covalent bond with AChE through phosphorylation and carbamoylation, respectively [ 67 ]. The inhibition of AChE leads to ACh accumulation that eventually results in over-stimulation of postsynaptic cholinergic receptors [ 76 ].…”
Section: Malaria Vector Controlmentioning
confidence: 99%
“…Most Lepidopteran insect larvae are phytophagous 2 and destructive, 3 resulting in severe production losses in agricultural and forestry crops, fruit trees, tea, vegetables, and flowers. Meanwhile, some Lepidopteran pests have developed high resistance to insecticides, 4 increasing the difficulty of prevention and control. Moreover, repeated application of insecticide chemicals negatively affects pesticide efficacy, soil microorganisms, environment safety, people's health, and other beneficial insects.…”
Section: Introductionmentioning
confidence: 99%